Exploration And Identification Of Microbes In Strawberry (Fragaria x ananassa Dutch.) Rhizosphere In The Pancasari Bedugul Bali Region - Putra, Gustu Widi; Ramona, Yan; Proborini, Meitini Wahyuni (Metamorfosa: Journal of Biological Sciences, 2020)
The main objective of this research was to isolate and identify microbes residing in the rhizosphere zone of strawberry ( Fragaria x ananassa Dutch.), cultivated at Pancasari village, Bedugul Bali. This was an explorative and descriptive research conducted from April to July 2018. Soil samples were collected from the rhizosphere of strawberry plants and microbes residing in them were isolated by applying dilution and platting method, purified, and identified at the Food Microbology Laboratory, Faculty of Agricultural Technology, Udayana University.  Important characteristics of the isolated microbes were compared to those specified in references, such as Bergey’s Manual of Determine Bacteriology 9 th Edition (Holt et al ., 1994) for bacterial isolates and Fungal Identification keys (Barnett and Hunter, 1972; dan Pitt and Hocking, 2009) for fungal isolates. Microbes successfully isolated and identified in this research included fungi and bacteria belong to Aspergillus flavus , Aspergillus niger , Fusarium oxysporum , and Colletotrichum sp., Pseudomonas sp., and Bacillus sp.     Keywords: rhizosphere, strawberry, microbes.